Reflection of Mo Limo Sunan Kalijaga on Regional Government Accountability - Salim, Ahmad; Mufarokah, Mufarokah; Suprianto, Edy (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to identify the philosophy of Sunan Kalijaga's mo limo reflected in the accountability of local government. This study uses a phenomenological approach with informants from the regional secretary and the caretaker of Sunan Kalijaga's tomb. The results of this study are that the main teachings of Sunan Kalijaga that are held firmly are Mo limo. Mo limo consists of Manembah, Mangabdi, Maguru, Makaryo and Martapa. The local government really embodies and actualizes the philosophy of Sunan Kalijaga in the implementation of governance. The implication is that the cultural value of local wisdom of a region needs to be considered to improve public accountability and transparency. The local government must continue to maintain local culture to improve the performance of the local government.